2012
DOI: 10.1021/je3001377
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Carbon Dioxide in Imidazolium-Based Ionic Liquids with a Methanesulfonate Anion

Abstract: For the halide-free imidazolium-based ionic liquids with a methanesulfonate anion, the solubility results of carbon dioxide (CO 2 ) are presented at pressures up to approximately 45 MPa and temperatures ranging from 303.15 K to 343.15 K. The solubility was determined by measuring bubble pressures of mixtures of CO 2 and ionic liquid using a high-pressure equilibrium apparatus equipped with a variable-volume view cell. The ionic liquids studied in this work were 1,3-dibutylimidazolium methanesulfonate, 1-ethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…First investigations of the absorption of H 2 S with the IL [EMIM][MeSO 3 ] in our working group showed that the IL can also absorb H 2 S 60. It is also known from the literature that CO 2 dissolves in this IL and thus can be removed from natural gas by absorbing 61–63. In addition, it should also be explored if the drying performance of the IL [EMIM][MeSO 3 ] is reduced in the presence of H 2 S and CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…First investigations of the absorption of H 2 S with the IL [EMIM][MeSO 3 ] in our working group showed that the IL can also absorb H 2 S 60. It is also known from the literature that CO 2 dissolves in this IL and thus can be removed from natural gas by absorbing 61–63. In addition, it should also be explored if the drying performance of the IL [EMIM][MeSO 3 ] is reduced in the presence of H 2 S and CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The rational design of the corresponding absorption system suitable for industrial scale-up purposes will require a precise knowledge of the physical equilibrium between CO 2 and the ionic liquid. A vast number of experimental works in the literature deal with CO 2 solubility in various kinds of ionic liquids at different temperature and pressure conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: June 2015mentioning
confidence: 99%
“…A schematic diagram of the experimental apparatus and a detailed description of the experimental procedure are given in our previous publications [12,13,[22][23][24]27]. The apparatus has a view cell equipped with a sapphire window and a movable piston, a pressure generator (High Pressure Equipment Co. model 50-6-15), a borescope (Olympus model R080-044-000-50), a magnetic stirring system, and an air bath.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…As there is no water present the increase in corrosion rates is attributed to the enhanced charge mobility by [bmim][MS]. CO 2 was physically absorbed on the ionic liquid, structural modification of imidazole cation is shown by the published data of Jung et al [33]. Increase in CO 2 absorption by longer chain cations than [bmim] further strengthens the view that the cation is a major source of CO 2 absorption.…”
Section: Tafel Curvesmentioning
confidence: 90%
“…The density data and molecular weight of the ionic liquid is used to estimate the critical properties of the hypothetical molecule. The solubility of the carbon dioxide in the ionic liquid is regressed as a polynomial, based on the data available in the literature [33] (at low pressure <5 MPa, it can be considered a straight line). The process using an ionic liquid is modeled as parallel to The immidazolium-based cation is functionalized and it is reported to increase CO 2 absorption by threefold for ionic liquids [40,41].…”
Section: Absorption Process With Ionic Liquidmentioning
confidence: 99%